Pengembangan E-Book Berbasis Problem Based Learning (PBL) untuk Meningkatkan Pemahaman Konsep Matematis pada Materi Persamaan Linear Satu Variabel (PLSV) Siswa Kelas VIII SMP - Alfiah Nabila Putri; Usman Mulbar (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2026)
This study was motivated by students’ low mathematical conceptual understanding caused by learning practices that still emphasize formula memorization. This condition indicates the need for innovative learning media that can help students understand mathematical concepts more deeply and contextually. The purpose of this study was to develop an interactive e-book based on Problem Based Learning (PBL) on the topic of Linear Equations in One Variable for eighth-grade junior high school students that is valid, practical, and effective in improving students’ mathematical conceptual understanding. This research employed the Research and Development (R&D) method using the ADDIE development model, consisting of the stages of analysis, design, development, implementation, and evaluation. Data were collected through expert validation sheets, teacher and student response questionnaires, and mathematical conceptual understanding tests. The data were analyzed using quantitative and qualitative descriptive analysis techniques. The results showed that the PBL-based e-book achieved a validity level of 92%, categorized as very valid. The practicality level based on teacher and student responses reached 89%, categorized as very practical. Furthermore, the effectiveness test indicated an improvement in students’ mathematical conceptual understanding with an average N-Gain score of 0.72, which falls into the high category. Therefore, the PBL-based e-book on Linear Equations in One Variable is feasible to be used as a digital teaching material to support more active, interactive, and meaningful mathematics learning.